Skin healing and scale regeneration in fed and unfed sea bream, Sparus auratus - Vieira, Florbela A (BioMed Central, 2011)
BACKGROUND: Fish scales are an important reservoir of calcium and phosphorus and together with the skin function as an integrated barrier against environmental changes and external aggressors. Histological studies have revealed that the skin and scales regenerate rapidly in fish when they are lost or damaged. In the present manuscript the histological and molecular changes underlying skin and scale regeneration in fed and fasted sea bream (Sparus auratus) were studied using a microarray 3 and 7 days after scale removal to provide a comprehensive molecular understanding of the early stages of these processes. RESULTS: Histological analysis of skin/scales revealed 3 days after scale removal re-epithelisation and formation of the scale pocket had occurred and 53 and 109 genes showed significant up or down-regulation, respectively. Genes significantly up-regulated were involved in cell cycle regulation, cell proliferation and adhesion, immune response and antioxidant activities. 7 days after scale removal a thin regenerated scale was visible and only minor changes in gene expression occurred. In animals that were fasted to deplete mineral availability the expression profiles centred on maintaining energy homeostasis. The utilisation of fasting as a treatment emphasised the competing whole animal physiological requirements with regard to barrier repair, infection control and energy homeostasis. CONCLUSIONS: The identification of numerous genes involved in the mitotic checkpoint and cell proliferation indicate that the experimental procedure may be useful for understanding cell proliferation and control in vertebrates within the context of the whole animal physiology. In response to skin damage genes of immune surveillance were up-regulated along with others involved in tissue regeneration required to rapidly re-establish barrier function. Additionally, candidate fish genes were identified that may be involved in cytoskeletal re-modelling, mineralization and stem cells, which are of potential use in aquaculture and fish husbandry, as they may impact on the ability of the fish to produce structural proteins, such as muscle, efficiently.